Maladaptive Cognitive Bias in the New Normal Period: An Analyses from a Behavioural Science Perspective in the Time of Covid-19 - Zafira Rahmania Nur Shabrina; Insan Rekso Adiwibowo; Nurul Aisya Beryllia (Faculty of Psychology Universitas Gadjah Mada, 2020)
The limited number of effective medical interventions to combat Covid-19 to date has resulted in government institutions focusing on preventive behaviours believed to minimize virus transmission. The Indonesian government has launched a ‘new normal’ campaign whereby outdoor activities are restricted by various health protocols established by health authorities, such as wearing a mask, habitual hand washing and social distancing. However, these protocols have not been implemented with a thorough understanding of human behaviour. The result is numerous violations of the protocol, which subsequently lead to the persistence of Covid-19 cases in Indonesia. Behavioural science as an approach can provide important insights regarding the systematic errors of thought that contribute to non-compliance with Covid-19 health signs. This article will elaborate on the different types of systematic errors, known as cognitive biases, that plays a role in Covid-19 protocol compliance and suggest the corresponding solutions deemed most effective to overcome these obstacles. Understanding of the dynamics paired with the application of behaviourally informed strategies will hence contribute to the attempt to flatten the Covid-19 curve.